Micro autonomous underwater vehicle - Lim, Kok Wee (2016)
Coral reef monitoring project has gained its momentum in the world when the world population starts to realise the effect of global warming and pollution. Constant coral reef monitoring project requires human divers to observe and monitor at a very high frequency to observe the effect of human activities to the coral reef. The usage of autonomous underwater vehicle (AUV) has proven its efficiency and its benefit in reducing the risk and lengthen the monitoring time of coral reef. An existing underwater vehicle with dynamic diving principle is adopted for this research, whereby the electronic components have to be stored on board in a watertight electronics compartment. The design of watertight electronics compartment has been verified with finite element analysis that it is safe to work up to I Sm deep. Depth control simulation carried out in Matlab Simulink indicates the depth control of the AUV can be controlled using Proportional-Integral-Derivative (PID) controller. The designed hardware, both mechanical and electronics are fabricated and developed and implemented on the adopted underwater vehicle for validation purpose. Microcontroller is developed to control the AUV through a tether cable.